Al-Jihad al-T'alimi- in search of a united front in Educational Jihad and the experience of Yoruba Muslims (2007)
This paper focuses on the early Muslim/Christian encounters in Yorubaland in Nigeria and how Yoruba Muslims were united in their intellectual and missionary activities in their quest to stop the conversion of Muslims by early Christian missionaries. The paper traces the origin and development of Islamic organizations in Nigeria to the desires of Muslims to be educated without being converted to Christianity by missionaries who pioneered the modern school system in Nigeria. While the Muslim/Christian encounter has on many occasions, been characterized by antagonistic, bitter and aggressive relationship, it has also witnessed periods of peaceful interfaith coexistence and competition. This paper also examines the attitudes of Yoruba Muslims as exponents of interfaith intellectual friendship and competition towards Christian educational evangelism in Nigeria both in the colonial and post-colonial eras. It argues that this Yoruba disposition is the outcome of their united perception of the concept of Jihad in Islam. Finally, the paper reveals the need for Islamic organizations that have founded Islamic schools to be actively involved in sustaining this ummatic spirit of unity by continuously upholding the Yoruba Muslim interfaith intellectualism.